Entrepreneurship For Sustainable Development in Nigeria - Bamgboye, Patrick Oluseun (Advances in Social Sciences Research Journal, 2024)
The study observes that entrepreneurship in Nigeria is constrained by the challenges inherent in the business environment, thereby impacting negatively on the sustainable development of the country. These challenges range from limited access to capital or credit and inadequate or epileptic power (electricity) supply among others to adequately run businesses. Entrepreneurship as it were is the greatest potential to contribute significantly to the sustainable development of any nation, and most especially Nigeria. It is the contention of this study on the one hand that entrepreneurs themselves should operate within the legitimate business environment that is guided by rules and regulations, while the government on the other hand, should provide a conducive business environment through appropriate policies and regulations for businesses to thrive. By this, we believe entrepreneurship will be a catalyst for the sustainable development of the country.